2010
DOI: 10.1016/j.jcrs.2010.06.056
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical parameters of the cornea after collagen crosslinking measured by waveform analysis

Abstract: Although previous in vitro studies found a change in corneal rigidity, this study found no significant change in CH or CHF measured by biomechanical waveform analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
43
0
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(50 citation statements)
references
References 19 publications
4
43
0
3
Order By: Relevance
“…Ultrasound measurements on in vitro human corneas provided a value of 5.3 MPa, 21 and an in vivo approach based on the deformation with applanation tonometry 0.29 MPa in humans. 22 The large differences across reports of Young's modulus likely arise from the different working principles of the techniques, and the hydration condition in which corneal tissue is measured.…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasound measurements on in vitro human corneas provided a value of 5.3 MPa, 21 and an in vivo approach based on the deformation with applanation tonometry 0.29 MPa in humans. 22 The large differences across reports of Young's modulus likely arise from the different working principles of the techniques, and the hydration condition in which corneal tissue is measured.…”
Section: Discussionmentioning
confidence: 99%
“…There were no significant differences in corneal biomechanical properties as measured with the parameters CH and CRF. 15 In another study, Sedaghat et al 16 compared CH and CRF before and after CXL for KC and concluded that although previous in vitro studies found a change in corneal rigidity, their study found no significant change in CH or CHF measured by biomechanical waveform analysis. These results were echoed in a study by Gkika et al, in which no significant change in the CRF parameters were found in keratoconic eyes before and after riboflavin/ UVA corneal CXL.…”
Section: Clinical Evaluation Of the Biomechanical Changes Occurring Imentioning
confidence: 98%
“…После УФ-сшивания величина эластичности роговицы становится еще меньше [46]. Тогда как, по сведениям M. Sedaghat и соавт., повышенная после кросслинкинга жесткость ро-говиц не влияет на данные корнеального коэффициента резистентности и гистерезиса у пациентов до и через 6 мес после процедуры [47].…”
Section: биомеханика роговицы при уф-кросслинкингеunclassified